(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2019)
It is emphasized in the article that I. Franko constantly kept in sight the multifaceted creativity of M. Kropyvnytskyi. The critic highly appreciated the theatre created by M. Kropyvnytskyi on the eastern territories of Ukraine, he considered M. Kropyvnytskyi to be a coryphaeus of the national dramatic art. It is noted that the influence of M. Kropyvnytskyi on I. Franko’s dramatic works, in particular in the drama «Uchitel’» («A Teacher») is significant.